Biblical Archaeology for the People: Bridging the Scholary - Popular Divide - Cline, Eric H. (The Biblical archaeology review, 2021)
The Biblical Archaeology Society aims to educate the public about archaeology and the Bible. BAR interviewed three educators who share this vision—Eric H. Cline of the George Washington University, Melissa Cradic of the Badè Museum, and Jodi Magness of the University of North Carolina at Chapel Hill—on the importance of public scholarship and new directions in the field.